The Remarriage in Emete Village: Socio-Economic Impacts and Islamic Law Perspectives - Wardah, Andi; Faisal, Faisal; Yamin, Ade (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2024)
Remarriages are often found in big cities or developed regions. However, the phenomenon of remarriage is common in a remote village in Emete Village, Obaa District, Mappi Regency, South Papua Province. This study investigates the phenomenon of remarriage among women in Emete Village, Obaa District, Mappi Regency, South Papua, focusing on the socio-economic and cultural dynamics that drive such practices and their implications under Islamic law. Unlike the widely studied contexts of urban and developed regions, remarriages in this remote village present unique challenges and cultural nuances. The study explores key questions: what factors compel women in Emete Village to remarry, and how do these marriages align with Islamic principles? Utilizing qualitative research with an ethnographic approach, data were collected through in-depth interviews, observations, and analysis of religious and social practices. The findings reveal two forms of remarriage: those following legal divorces and those occurring without formal divorce, each shaped by economic pressures, failed previous marriages, and the quest for social recognition. Further, the study underscores the significant legal, social, and economic implications, including non-compliance with iddah (waiting period) rules, lack of financial justice, and risks associated with unregistered marriages. These practices challenge Islamic principles concerning fairness, legal status, and protection for women and children. This research contributes to the broader discourse on Islamic family law by highlighting the need for integrative socio-religious solutions to address the complexities of remarriage in remote communities.